Low-metal friction material for racing car as well as preparation method, brake pad and application of low-metal friction material
By using phenolic resin modified stainless steel, composite rubber and other materials in low-metal friction materials, combined with cold pressing and curing treatment, the shortcomings of existing low-metal friction materials in wear resistance, noise, thermal stability and braking pressure are solved, and the stability performance of the material and a simplified preparation process are achieved.
Patent Information
- Application Number
- CN202510176235.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-18
- Publication Date
- 2025-03-25
AI Technical Summary
The existing low-metal friction materials have shortcomings in wear resistance, noise, thermal stability and braking pressure, and the preparation process is complex, resulting in high production costs.
The combination of phenolic resin modified stainless steel, composite rubber, lubricating materials, friction enhancing materials and fillers is used to prepare low-metal friction materials through cold pressing and curing treatment to ensure the stable friction coefficient, excellent wear resistance, low noise and thermal stability of the material.
The stable friction coefficient, excellent wear resistance, low noise and excellent thermal stability of low metal friction materials are achieved, which reduces braking pressure, simplifies the preparation process, and reduces production costs.
Smart Images

Figure CN119683903A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of brake pad materials, and in particular relates to a low-metal friction material for racing cars, a preparation method thereof, a brake pad and applications thereof. Background Art
[0002] Low-metal friction material is a friction material composed of a variety of materials, in which the metal component accounts for a relatively low proportion. Although the existing low-metal friction materials have improved wear resistance, their wear rate is still higher than that of some other types of friction materials. They may produce loud noises during braking, and a certain degree of thermal decay may still occur when braking for a long time at high temperatures. In addition, since the internal metal content of low-metal friction materials is low and the strength is high, higher braking pressure may be required during braking to achieve the same braking effect. This may place a greater burden on other components of the brake system and may affect the response speed and sensitivity of the brakes.
[0003] In addition, since low metal friction materials require the use of more special raw materials and additives, and since both organic and inorganic materials exist, in order to ensure the quality and performance of the final product during preparation, it is necessary to improve the compatibility between organic and inorganic materials. Therefore, the preparation process control is relatively complex, which leads to an increase in production costs. Summary of the invention
[0004] To solve the above problems, the present invention provides a low-metal friction material for racing cars, a preparation method thereof, a brake pad and applications thereof. The low-metal friction material has a stable friction coefficient, excellent wear resistance, low noise and excellent thermal stability.
[0005] The present invention is achieved through the following technical solutions: In a first aspect, the present invention provides a low metal friction material for racing cars, comprising the following raw materials in parts by weight: , In some possible implementations, the phenolic resin modified stainless steel includes the following raw materials in parts by weight: 3 to 5 parts of phenolic resin, 1 to 2 parts of aramid pulp, 9 to 15 parts of silane coupling agent, and 7 to 15 parts of stainless steel powder.
[0006] In some possible implementations, the stainless steel powder is composed of the following raw material components in mass fractions: 2%~3% aluminum, 0.5%~0.8% copper, 0.01%~0.05% cerium, 0.2%~0.6% silicon carbide, and the balance is iron and inevitable impurities.
[0007] In some possible implementations, the composite rubber includes the following raw materials in parts by weight: 2~3 parts natural rubber and 4~8 parts synthetic rubber.
[0008] In a second aspect, the present invention provides a method for preparing the above-mentioned low-metal friction material for racing cars, comprising the following steps: The mixed raw materials are subjected to cold pressing and curing treatment to obtain the low metal friction material; The mixed raw materials include: phenolic resin modified stainless steel, composite rubber, lubricating material, friction increasing material and filler.
[0009] In some possible implementations, preparing the phenolic resin modified stainless steel comprises the following steps: The silane coupling agent and stainless steel powder are mixed, and then mixed with phenolic resin and aramid pulp to obtain the phenolic resin modified stainless steel.
[0010] In some possible implementations, the step of mixing with phenolic resin and aramid pulp includes: Under the conditions of a stirring speed of 2000 rpm to 3000 rpm and a mixing temperature of 55°C to 75°C, phenolic resin and aramid pulp are added respectively, and stirring is continued for 10 min to 30 min.
[0011] In some possible implementations, preparing the mixed raw material includes the following steps: Phenolic resin modified stainless steel, composite rubber, lubricating material, friction increasing material and filler are mixed and melt extruded at 150°C to 160°C.
[0012] In some possible implementations, in the cold pressing process, the cold pressing temperature is 110° C. to 140° C., the cold pressing pressure is 90 MPa to 100 MPa, and the cold pressing holding time is 5 min to 10 min.
[0013] In a third aspect, the present invention provides a brake pad, comprising the low metal friction material for racing provided by the present invention.
[0014] In a fourth aspect, the present invention provides an application of the low metal friction material for racing provided by the present invention in racing car parts.
[0015] Compared with the prior art, the low-metal friction material for racing cars, the preparation method thereof, the brake pad and the application thereof provided by the present invention have at least the following beneficial technical effects: (1) The low-metal friction material for racing cars provided by the present invention comprises phenolic resin modified stainless steel, which can be well mixed with composite rubber, lubricating material, friction-increasing material and filler; the phenolic resin modified stainless steel has good corrosion resistance and mechanical properties; the composite rubber comprises natural rubber and synthetic rubber, which can balance the elasticity and wear resistance of the low-metal friction material. The synergistic effect of the phenolic resin modified stainless steel, the composite rubber, the lubricating material, the friction-increasing material and the filler enables the low-metal friction material to have a stable friction coefficient, excellent wear resistance, low noise and excellent thermal stability.
[0016] (2) The method for preparing the low metal friction material for racing car provided by the present invention has a simple preparation process and is easy to implement. BRIEF DESCRIPTION OF THE DRAWINGS In order to more clearly illustrate the embodiments of the present drawings or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present drawings. For ordinary technicians in this field, other drawings can be obtained based on the structures shown in these drawings without paying any creative work. Figure 1 Schematic diagram of noise performance curve of low metal friction material / metal friction material provided in Example 1 and Comparative Example 1 of the present invention. The purpose, features and advantages of this figure will be further described in conjunction with the embodiments with reference to the accompanying drawings. DETAILED DESCRIPTION
[0017] In order to make the purpose, technical scheme and advantages of the present invention clearer, the present invention is described and illustrated in conjunction with the embodiments below. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not intended to limit the present invention. Based on the embodiments provided by the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work belong to the scope of protection of the present invention.
[0018] Obviously, the following descriptions are only some examples or embodiments of the present invention, and for those of ordinary skill in the art, the present invention can also be applied to other similar scenarios without creative work. In addition, it can also be understood that although the efforts made in such a development process may be complex and lengthy, for those of ordinary skill in the art related to the contents disclosed in the present invention, some changes in design, manufacturing or production based on the technical contents disclosed in the present invention are just conventional technical means, and should not be understood as the contents disclosed in the present invention being insufficient.
[0019] However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially the same structures may be omitted. This is to avoid the following description from becoming unnecessarily lengthy and to facilitate understanding by those skilled in the art. In addition, the following description is provided for those skilled in the art to fully understand the present invention and is not intended to limit the subject matter described in the claims.
[0020] If not otherwise specified, all embodiments and optional embodiments of the present invention may be combined with each other to form a new technical solution, and all technical features and optional technical features of the present invention may be combined with each other to form a new technical solution.
[0021] The following is a detailed description of a low-metal friction material for racing cars and a preparation method thereof, and a brake pad according to an embodiment of the present invention.
[0022] A first aspect of an embodiment of the present invention provides a low metal friction material for racing cars, comprising the following raw materials in parts by weight: , The low metal friction material for racing cars provided by the embodiment of the present invention comprises phenolic resin modified stainless steel and composite rubber, which can be well mixed with lubricating material, friction increasing material and filler; the synergistic effect of phenolic resin modified stainless steel, composite rubber, lubricating material, friction increasing material and filler makes the low metal friction material have a stable friction coefficient, excellent wear resistance, low noise and excellent thermal stability.
[0023] In the embodiment, the weight percentage of the phenolic resin modified stainless steel is 18 to 35 parts, which can be 18, 20, 28, 35, or other typical but non-limiting weight percentages or a range between any two weight percentages. In this case, the phenolic resin modified stainless steel has good corrosion resistance and mechanical properties.
[0024] In the embodiment, the weight percentage of the composite rubber is 1 to 5 parts, which can be 1, 2, 3, 4, 5, or other typical but non-limiting weight percentages or a range between any two weight percentages. In this case, the composite rubber can balance the elasticity and wear resistance of the low metal friction material.
[0025] In the embodiment, the weight proportion of the lubricating material is 15 to 25 parts, which can be 15, 18, 20, 25, or other typical but non-limiting weight proportions or a range between any two weight proportions. In this case, the lubricating material can stabilize the friction coefficient of the low metal friction material, making the braking performance more reliable. In addition, the lubricating material can also improve the anti-scratch, anti-bite and anti-adhesion properties of the brake pad, and prevent adhesion or bite between the brake pad and the mating part.
[0026] In the embodiment, the weight percentage of the friction-increasing material is 25 to 30 parts, which can be 25, 28, 30, or other typical but non-limiting weight percentages or a range between any two weight percentages. In this case, the friction-increasing material can improve the friction coefficient and wear resistance of the low-metal friction material and extend its service life.
[0027] In the embodiment, the weight percentage of the filler is 20 to 30 parts, which can be 20, 25, 30, etc. typical but non-limiting weight percentages or a range between any two weight percentages. In this case, the filler can adjust the friction performance and wear resistance of the low metal friction material, improve the brake noise, etc.
[0028] In some embodiments, the phenolic resin modified stainless steel includes the following raw materials in parts by weight: 3 to 5 parts of phenolic resin, 1 to 2 parts of aramid pulp, 9 to 15 parts of silane coupling agent, and 7 to 15 parts of stainless steel powder.
[0029] In this case, stainless steel is grafted with phenolic resin and aramid pulp through silane coupling agent, which improves the mixing uniformity between stainless steel and other materials in low metal friction materials, thereby improving the heat resistance, mechanical properties, wear resistance, impact resistance, etc. of stainless steel.
[0030] In some embodiments, the phenolic resin is BMJ-91, BMJ-92, or BMJ-93.
[0031] In some embodiments, the aramid pulp is Kevlar aramid pulp (1F1710 or 1F538) produced by DuPont.
[0032] In some embodiments, the silane coupling agent includes at least one of acetyltrimethoxysilane, γ-aminopropyltriethoxysilane (KH-550), γ-aminopropyltrimethoxysilane (KH-551), and γ-(2,3-glycidyloxy)propyltrimethoxysilane (KH-560).
[0033] In some embodiments, the stainless steel powder is composed of the following raw material components in mass fractions: 2%~3% aluminum, 0.5%~0.8% copper, 0.01%~0.05% cerium, 0.2%~0.6% silicon carbide, and the balance is iron and inevitable impurities. In this case, aluminum, copper, cerium and silicon carbide work together to make the stainless steel powder have excellent wear resistance and corrosion resistance.
[0034] In some embodiments, the average particle size of the stainless steel powder is 100 nm to 500 nm. In the exemplary embodiment, the average particle size can be 100 nm, 300 nm, 500 nm, or any range between two average particle sizes. In this case, the average particle size of the phenolic resin modified stainless steel made from the stainless steel powder can reach the micron level or even the nanometer level.
[0035] In some embodiments, the composite rubber includes the following raw materials in parts by weight: 2 to 3 parts of natural rubber and 4 to 8 parts of synthetic rubber. In this case, natural rubber and synthetic rubber work together to balance the elasticity and wear resistance of low metal friction materials.
[0036] In some embodiments, the natural rubber origin is selected from Malaysia.
[0037] In some embodiments, the synthetic rubber includes at least one of nitrile rubber, styrene butadiene rubber, and polyurethane rubber.
[0038] In some specific embodiments, the average molecular weight of the nitrile rubber is 500,000 to 700,000.
[0039] In some specific embodiments, the average molecular weight of the styrene-butadiene rubber is 400,000 to 600,000.
[0040] In some specific embodiments, the average molecular weight of the polyurethane rubber is 600,000 to 800,000.
[0041] In some embodiments, the lubricating material includes at least one of graphene nanosheets and nano-silicon dioxide. In this case, the graphene nanosheets have excellent high temperature resistance, friction reduction and anti-wear properties, and the nano-silicon dioxide can improve the corrosion resistance, mechanical strength and wear resistance of the low metal friction material.
[0042] In some embodiments, the diameter of the graphene nanosheets is 5 μm to 10 μm.
[0043] In some embodiments, the average particle size of nano-silica is 30 nm to 50 nm.
[0044] In some embodiments, the friction-increasing material includes at least one of nano-silicon carbide, nano-aluminum oxide, nano-zirconium oxide, and modified carbon nanotubes.
[0045] In some embodiments, the average particle size of nano-silicon carbide is 50 nm to 100 nm.
[0046] In some embodiments, the average particle size of nano-alumina is 50 nm to 100 nm.
[0047] In some embodiments, the average particle size of nano-zirconia is 50 nm to 100 nm.
[0048] In some embodiments, the modified carbon nanotubes are hydroxyl-modified carbon nanotubes. In this case, the modified carbon nanotubes have better wettability and dispersibility, which is beneficial for their uniform distribution in the composite material.
[0049] In some embodiments, the average diameter of the hydroxyl-modified carbon nanotubes is 30 nm to 40 nm.
[0050] In some embodiments, the filler includes at least two of talc, wollastonite, sepiolite, and molybdenite.
[0051] In some embodiments, the average particle size of talc is 50 μm to 150 μm.
[0052] In some embodiments, the average particle size of wollastonite is 50 μm to 150 μm.
[0053] In some embodiments, the average particle size of the sepiolite is 50 μm to 150 μm.
[0054] In some embodiments, the average particle size of the molybdenite is 50 μm to 150 μm.
[0055] A second aspect of the embodiment of the present invention provides a method for preparing a low metal friction material for racing cars provided by an embodiment of the present invention, comprising the following steps: S10. The mixed raw material is cold pressed and cured to obtain a low metal friction material; The mixed raw materials include: phenolic resin modified stainless steel, composite rubber, lubricating material, friction increasing material and filler.
[0056] The method for preparing the low metal friction material for racing car provided by the embodiment of the present invention has a simple preparation process and is easy to implement.
[0057] In some embodiments, in the above step S10, preparing phenolic resin modified stainless steel includes the following steps: S101. After mixing the silane coupling agent and the stainless steel powder, the mixture is mixed with the phenolic resin and the aramid pulp to obtain the phenolic resin modified stainless steel.
[0058] In some embodiments, in the above step S101, when the silane coupling agent and the stainless steel powder are mixed, the stirring speed is 20 rpm to 30 rpm and the mixing temperature is 25° C. to 35° C.
[0059] In some embodiments, in the above step S101, the step of mixing with phenolic resin and aramid pulp includes: Under the conditions of a stirring speed of 2000 rpm to 3000 rpm and a mixing temperature of 55°C to 75°C, phenolic resin and aramid pulp are added respectively, and stirring is continued for 10 min to 30 min.
[0060] In some embodiments, in the above step S10, preparing the mixed raw material includes the following steps: Phenolic resin modified stainless steel, composite rubber, lubricating material, friction increasing material and filler are mixed and melt extruded at 150°C to 160°C.
[0061] In some embodiments, in the above step S10, during the cold pressing process, the cold pressing temperature is 110° C. to 140° C., the cold pressing pressure is 90 MPa to 100 MPa, and the cold pressing holding time is 5 min to 10 min.
[0062] In some embodiments, in the above step S10, during the curing process, the curing temperature is 170° C. to 190° C. and the curing time is 6 h to 12 h.
[0063] A third aspect of an embodiment of the present invention provides a brake pad, comprising the low-metal friction material for racing provided by an embodiment of the present invention.
[0064] The following is a further explanation with reference to specific examples. The phenolic resin used in the following examples is BMJ-91; the aramid pulp is Kevlar aramid pulp 1F1710 produced by DuPont; and the origin of natural rubber is selected from Malaysia.
[0065] Example 1 Embodiment 1 provides a low metal friction material for racing cars, which is composed of the following components in parts by weight: 28 parts of phenolic resin modified stainless steel, 4 parts of composite rubber, 20 parts of graphene nanosheets (lubricating material), 28 parts of nano silicon carbide (friction increasing material), 20 parts of talc powder and 5 parts of wollastonite.
[0066] The phenolic resin modified stainless steel is composed of the following raw materials in parts by weight: 4 parts of phenolic resin, 1 part of aramid pulp, 10 parts of KH-560, and 8 parts of stainless steel powder; the raw material components of the stainless steel powder have a mass fraction of: 2% aluminum, 0.6% copper, 0.03% cerium, 0.5% silicon carbide, and the remainder is iron and unavoidable impurities; the average particle size of the stainless steel powder is 300nm; The composite rubber is composed of the following raw materials in parts by weight: 2 parts of natural rubber and 7 parts of nitrile rubber, wherein the average molecular weight of the nitrile rubber is 600,000; The diameter of graphene nanosheets is 10 μm; The average particle size of nano-silicon carbide is 80nm; The average particle size of talc is 50 μm; The average particle size of wollastonite is 50 μm.
[0067] This embodiment also provides a method for preparing the low metal friction material for racing cars provided in this embodiment, the steps are as follows: E01. Preparation of phenolic resin modified stainless steel: KH-560 and stainless steel powder were mixed at a stirring speed of 25 rpm and a mixing temperature of 25°C; then, phenolic resin and aramid pulp were added respectively at a stirring speed of 2500 rpm and a mixing temperature of 65°C, and stirring was continued for 30 minutes.
[0068] E02. Preparation of composite rubber: Natural rubber and nitrile rubber were mixed and melted and extruded at a stirring speed of 2000 rpm and a temperature of 150°C.
[0069] E03. The mixed raw materials are cold pressed and cured to obtain a low metal friction material; Among them, in the cold pressing treatment, the cold pressing temperature is 130°C, the cold pressing pressure is 90MPa, and the cold pressing holding time is 8min; During the curing process, the curing temperature was 180° C. and the curing time was 10 h.
[0070] Example 2 Embodiment 2 provides a low metal friction material for racing cars, which is composed of the following components in parts by weight: 20 parts of phenolic resin modified stainless steel, 3 parts of composite rubber, 18 parts of nano silicon dioxide (lubricating material), 30 parts of nano silicon carbide (friction increasing material), 15 parts of wollastonite (filler) and 15 parts of molybdenite (filler).
[0071] The phenolic resin modified stainless steel is composed of the following raw materials in parts by weight: 5 parts of phenolic resin, 2 parts of aramid pulp, 15 parts of KH-560, and 15 parts of stainless steel powder; the raw material component composition and mass fraction of the stainless steel powder are the same as those in Example 1; the average particle size of the stainless steel powder is 500 nm; The composite rubber is composed of the following raw materials in parts by weight: 3 parts of natural rubber and 8 parts of nitrile rubber; The average particle size of nano-silicon dioxide is 40nm; The average particle size of nano-silicon carbide is 50nm; The average particle size of wollastonite is 50 μm; The average particle size of molybdenite is 50 μm.
[0072] This embodiment also provides a method for preparing the low metal friction material for racing cars provided in this embodiment, and the steps are the same as those in Embodiment 1.
[0073] Example 3 Embodiment 3 provides a low metal friction material for racing cars, which is composed of the following components in parts by weight: 18 parts of phenolic resin modified stainless steel, 1 part of composite rubber, 15 parts of graphene nanosheets (lubricating material), 10 parts of nano alumina (friction increasing material), 15 parts of nano zirconium oxide (friction increasing material), 10 parts of talc powder (filler) and 10 parts of sepiolite (filler).
[0074] The weight percentage of the raw materials of the phenolic resin modified stainless steel, the raw material component composition and the average particle size of the stainless steel powder are the same as those in Example 1; The raw material composition of the composite rubber in parts by weight is the same as that of Example 1; The diameter of graphene nanosheets is 5 μm; The average particle size of nano-alumina is 80nm; The average particle size of nano zirconium oxide is 80nm; The average particle size of talc is 100 μm; The average particle size of sepiolite is 100 μm.
[0075] This embodiment also provides a method for preparing the low metal friction material for racing cars provided in this embodiment, and the steps are the same as those in Embodiment 1.
[0076] Example 4 Embodiment 4 provides a low metal friction material for racing cars, which is composed of the following components in parts by weight: 35 parts of phenolic resin modified stainless steel, 5 parts of composite rubber, 25 parts of nano-silicon dioxide (lubricating material), 15 parts of nano-silicon carbide (friction-increasing material), 15 parts of hydroxyl-modified carbon nanotubes (friction-increasing material), 10 parts of talc powder (filler), 10 parts of wollastonite (filler) and 10 parts of sepiolite (filler).
[0077] The weight percentage of the raw materials of the phenolic resin modified stainless steel, the raw material component composition and the average particle size of the stainless steel powder are the same as those in Example 1; The raw material composition of the composite rubber in parts by weight is the same as that of Example 1; The average particle size of nano-silicon dioxide is 30nm; The average particle size of nano-silicon carbide is 100nm; The average particle size of hydroxyl-modified carbon nanotubes is 40 nm; The average particle size of talc is 150 μm; The average particle size of wollastonite is 150 μm; The average particle size of sepiolite is 150 μm.
[0078] This embodiment also provides a method for preparing the low metal friction material for racing cars provided in this embodiment, and the steps are the same as those in Embodiment 1.
[0079] Example 5 Embodiment 5 provides a low metal friction material for racing cars, which is composed of the following components in parts by weight: 35 parts of phenolic resin modified stainless steel, 5 parts of composite rubber, 10 parts of graphene nanosheets (lubricating material), 15 parts of nano silicon dioxide (lubricating material), 7 parts of nano silicon carbide (friction increasing material), 8 parts of nano alumina (friction increasing material), 7 parts of nano zirconium oxide (friction increasing material), 8 parts of hydroxyl modified carbon nanotubes (friction increasing material), 9 parts of talc (filler), 10 parts of wollastonite (filler), 7 parts of sepiolite (filler) and 4 parts of molybdenite (filler).
[0080] The weight percentage of the raw materials of the phenolic resin modified stainless steel, the raw material component composition and the average particle size of the stainless steel powder are the same as those in Example 1; The raw material composition of the composite rubber in parts by weight is the same as that of Example 1; The diameter of graphene nanosheets is 8 μm; The average particle size of nano-silicon dioxide is 50nm; The average particle size of nano-silicon carbide is 70nm; The average particle size of nano-alumina is 70nm; The average particle size of nano zirconium oxide is 70nm; The average particle size of hydroxyl-modified carbon nanotubes is 30 nm; The average particle size of talc is 80 μm; The average particle size of wollastonite is 80 μm; The average particle size of sepiolite is 80 μm; The average particle size of molybdenite is 80 μm.
[0081] This embodiment also provides a method for preparing the low metal friction material for racing cars provided in this embodiment, and the steps are the same as those in Embodiment 1.
[0082] Comparative Example 1 Comparative Example 1 provides a metal friction material, which is composed of the following components in parts by weight: 9 parts of phenolic resin, 7 parts of aramid pulp, 8 parts of stainless steel powder, 2 parts of natural rubber, 7 parts of nitrile rubber, 15 parts of lanthanum powder, 20 parts of graphene nanosheets (lubricating material), 28 parts of nano silicon carbide (friction increasing material), 20 parts of talc powder (filler) and 5 parts of wollastonite (filler).
[0083] Among them, the average particle size of stainless steel powder, the average molecular weight of nitrile rubber, the sheet diameter of graphene nanosheets, the average particle size of nano-silicon carbide, the average particle size of talc powder and the average particle size of wollastonite are the same as those in Example 1.
[0084] Comparative Example 2 Comparative Example 2 provides a metal friction material, which is composed of the following components in parts by weight: 9 parts of phenolic resin, 7 parts of aramid pulp, 8 parts of stainless steel powder, 4 parts of composite rubber, 20 parts of graphene nanosheets (lubricating material), 28 parts of nano silicon carbide (friction increasing material), 20 parts of talc powder (filler) and 5 parts of wollastonite (filler).
[0085] Among them, the average particle size of stainless steel powder, the material of composite rubber, the sheet size of graphene nanosheets, the average particle size of nano-silicon carbide, the average particle size of talcum powder and the average particle size of wollastonite are the same as those in Example 1.
[0086] Comparative Example 3 Comparative Example 3 provides a metal friction material, which is composed of the following components in parts by weight: 28 parts of phenolic resin modified stainless steel, 2 parts of natural rubber, 7 parts of nitrile rubber, 15 parts of lanthanum powder, 20 parts of graphene nanosheets (lubricating material), 28 parts of nano silicon carbide (friction increasing material), 20 parts of talc powder (filler) and 5 parts of wollastonite (filler).
[0087] Among them, the material of phenolic resin modified stainless steel, the average molecular weight of nitrile rubber, the average particle size of lanthanum powder, the sheet size of graphene nanosheets, the average particle size of nano-silicon carbide, the average particle size of talc powder and the average particle size of wollastonite are the same as those in Example 1.
[0088] In order to verify the advancement of a low metal friction material for racing provided by an embodiment of the present invention and a preparation method thereof, the following performance test experiments were conducted on the low metal friction material for racing provided by the embodiment and the metal friction material of the comparative example: (1) According to standard GB 5763, the friction coefficient (μ) and wear rate (δ, %) of low metal friction material / metal friction material were tested at high temperatures of 232°C, 260°C, 288°C, 316°C, and 343°C and a pressure of 30 bar. The results are shown in Table 1 below.
[0089] (2) According to standard SAE J2522, the shear strength of low metal friction material / metal friction material is tested at 300°C, as shown in Table 2 below.
[0090] (3) Taking Example 1 and Comparative Example 1 as examples, the noise performance of low metal friction material / metal friction material was tested, as shown in the attached manual. Figure 1 shown.
[0091] .
[0092] .
[0093] From Table 1~2 above and the instruction manual Figure 1 At least you can get: (1) In Table 1, the friction coefficients of the low-metal friction material for racing cars provided by the embodiment of the present invention at high temperatures of 232°C, 260°C, 288°C, 316°C, and 343°C are slightly different. It can be seen that the low-metal friction material for racing cars provided by the embodiment of the present invention has a stable friction coefficient.
[0094] (2) In Table 1, the wear rate of a low-metal friction material for racing car provided by an embodiment of the present invention at high temperatures of 232°C, 260°C, 288°C, 316°C and 343°C is very low. It can be seen that the low-metal friction material for racing car provided by an embodiment of the present invention has excellent wear resistance.
[0095] (3) In Table 2, the low metal friction material for racing provided by the embodiment of the present invention has a shear strength of more than 3.12 MPa at high temperature (300°C). Therefore, the low metal friction material for racing provided by the embodiment of the present invention has excellent thermal stability, thereby extending the service life of the material.
[0096] (4) Attached to the instruction manual Figure 1 It can be obtained that the noise generation rate of the low metal friction material for racing provided by the embodiment of the present invention is 0.36%, which is graded as AAA, while the noise generation rate of the metal friction material provided by Comparative Example 1 is 7.75%, which is graded as BBB. Therefore, the low metal friction material for racing provided by the embodiment of the present invention has the advantage of low noise.
[0097] It should be noted that the present invention is not limited to the above-mentioned embodiments. The above-mentioned embodiments are only examples, and the embodiments having the same structure as the technical idea and exerting the same effect within the scope of the technical solution of the present invention are all included in the technical scope of the present invention. In addition, without departing from the scope of the main purpose of the present invention, various modifications that can be thought of by those skilled in the art to the embodiments and other methods of combining some of the constituent elements in the embodiments are also included in the scope of the present invention.
Claims
1. A low metal friction material for racing car, characterized in that: The invention comprises the following raw materials in parts by weight: , The phenolic resin modified stainless steel includes the following raw materials in parts by weight: 3 to 5 parts of phenolic resin, 1 to 2 parts of aramid pulp, 9 to 15 parts of silane coupling agent, 7 to 15 parts of stainless steel powder; The composite rubber includes the following raw materials in parts by weight: 2~3 parts natural rubber, 4~8 parts synthetic rubber.
2. A method for preparing a low-friction metal material for racing car according to claim 1, characterized in that: The steps include: The mixed raw materials are subjected to cold pressing and curing treatment to obtain the low metal friction material; The mixed raw materials include: phenolic resin modified stainless steel, composite rubber, lubricating material, friction increasing material and filler.
3. The method for preparing a low-friction metal material for racing car according to claim 2, characterized in that: The preparation of the phenolic resin modified stainless steel comprises the following steps: The silane coupling agent and stainless steel powder are mixed, and then mixed with phenolic resin and aramid pulp and dried to obtain the phenolic resin modified stainless steel.
4. The method for preparing a low-friction metal material for racing car according to claim 3, characterized in that: The step of mixing with phenolic resin and aramid pulp comprises: Under the conditions of a stirring speed of 2000 rpm to 3000 rpm and a mixing temperature of 55°C to 75°C, phenolic resin and aramid pulp are added respectively, and stirring is continued for 10 min to 30 min.
5. The method for preparing a low-metal friction material for racing car according to any one of claims 2 to 4, characterized in that: The preparation of the mixed raw material comprises the following steps: Phenolic resin modified stainless steel, composite rubber, lubricating material, friction increasing material and filler are mixed and melt extruded at 150°C to 160°C.
6. The method for preparing a low-friction metal material for racing car according to claim 5, characterized in that: In the cold pressing treatment, the cold pressing temperature is 110° C. to 140° C., the cold pressing pressure is 90 MPa to 100 MPa, and the cold pressing holding time is 5 min to 10 min.
7. A brake pad, characterized in that: The invention comprises the low metal friction material for racing car as claimed in claim 1.
8. Use of the low metal friction material for racing car according to claim 1 in racing car parts.
Citation Information
Cited By
Preparation method of aramid phenolic resin composite material
CN121271152A
Preparation method of aramid phenolic resin composite material
CN121271152B